2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34121
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Systematic Reviews in the Engineering Literature

Abstract: is the Engineering Librarian at the University of Alberta. She earned a Bachelor's degree in Chemical Engineering from Queen's University and spent several years working in Environmental Health and Safety in the Chemical Industry before obtaining her MLIS. Her research interests focus on research impact analysis, and information literacy in engineering education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…These methodologies require thorough, replicable searching and transparent reporting, allowing the reviewer to synthesize the literature in order to answer specific research questions. Systematic reviews are extremely important in medical subject areas, with their emphasis on standards of evidence for clinical decision-making, and they are both increasingly prevalent in that literature and increasingly attractive to researchers in other subject areas, , with their emphasis on transparency and reproducibility and their ability to synthesize work from multiple complementary disciplines. While systematic reviews are not currently common in chemical health and safety, the field’s interdisciplinary nature could make this methodology appealing.…”
Section: Types Of Review Articlesmentioning
confidence: 99%
“…These methodologies require thorough, replicable searching and transparent reporting, allowing the reviewer to synthesize the literature in order to answer specific research questions. Systematic reviews are extremely important in medical subject areas, with their emphasis on standards of evidence for clinical decision-making, and they are both increasingly prevalent in that literature and increasingly attractive to researchers in other subject areas, , with their emphasis on transparency and reproducibility and their ability to synthesize work from multiple complementary disciplines. While systematic reviews are not currently common in chemical health and safety, the field’s interdisciplinary nature could make this methodology appealing.…”
Section: Types Of Review Articlesmentioning
confidence: 99%
“…Structured reviews -a formalized process to synthesize evidence-based practice and policy by extracting and analyzing research data from the scientific literature -are widely used in the fields of healthcare, social sciences, education, and economics, where humans are part of the system of study observed and manipulated by basic and applied researchers [1]. Structured reviews often are part of "translational medicine", where discoveries at the "lab bench" are brought to the "bed side".…”
Section: Introductionmentioning
confidence: 99%